Chairside Restorations of Maxillary Anterior Teeth with CAD/CAM Porcelain Laminate Veneers Produced by Digital Workflow: A Case Report with a Step to Facilitate Restoration Design - Elif Öztürk Bayazıt; Murat Karabıyık (Case Reports in Dentistry)
Since the introduction of porcelain laminate veneers in the early 1980s, the anterior esthetic rehabilitation with PLVs has been provided with a conventional restorative technique for many years. Recently, a new concept named digital workflow has been raised that will lead to the abandonment of conventional procedures during the fabrication of PLVs. Digital workflow is a new concept facilitating applications by adapting digital systems to clinical applications, including intra- and extraoral photographs, diagnostic wax-up, mock-up, intraoral camera, and use of the CAD/CAM device. The aim of this case report is to describe the clinical procedures of porcelain laminate veneers using digital workflow with a facilitating step in a single session and to evaluate the PLVs after one year of clinical service.